Solid Phase Extraction of Hg(II) from Environmental Samples - Wu, Chunlai; Peng, Chuanyun (Asian Journal of Chemistry, 2012)
This study investigates application of alizarin violet functionalized silica gel as an adsorbent for solid phase extraction of Hg(II) from enviromental water samples. Hg(II) can be easily separated and pre-concentrated in the presence of common coexisting ions. The influences of analytical parameters including pH of the aqueous solution, amount of the functionalized silica gel, stirring time and flow rates of sample solutions on the quantitative recoveries of Hg(II) were investigated. At the optimum conditions, Hg(II) can be adsorbed with almost 100 % retention, the adsorption equilibration for Hg(II) was achieved within 10 minutes and the adsorption capacity of the sorbent for Hg(II) is 6.38 mmol/g of dry functionalized silica gel. For Hg(II) solution of 10 ng mL-1, the pre-concentration factor is as high as 333 and the recovery is higher than 96 %. The new solid phase extractant has been used for the pre-concentration of low level of Hg(II) in different water samples with high recoveries. The self made chromatographic column can be reused for 50 times and the recovery of Hg(II) is higher than 95 %.